Origin and tectonic implications of ferroan alkali-calcic granitoids from the Hawal Massif, east-eastern Nigeria terrane: clues from geochemistry and zircon U-Pb-Hf isotopes. Issue 2 (22nd January 2020) - Ibrahim Bute, Saleh; Yang, Xiaoyong; Cao, Jingya; Liu, Lei; Deng, Jianghong; Vela Haruna, Ismaila; Girei, Musa Bala; Abubakar, Usman; Akhtar, Shamim
ABSTRACT: Late Cryogenian to Ediacaran magmatism of the East-Eastern Nigerian Terrane (E-ENT) in the Pan-African mobile belt provides a critical geological record that is important for unravelling regional tectonic and geodynamic setting. A detailed study that utilizes whole-rock elemental, in-situ zircon U-Pb and Lu-Hf isotopic geochemistry are conducted on the post-collisional granitoids from the Hawal Massif in the E-ENT. These granitoids are metaluminous to slightly peraluminous, alkali-calcic to calc-alkalic and ferroan in composition. U-Pb zircon ages suggest two granitic plutons were emplaced at 627 ± 4 Ma and ca. 580 Ma. Typically, these rocks are characterized by ƐHf (t) values ranging from +3 to -9.03 and T C DM ages range from 1.3 to 2.1 Ga, suggesting mixing of juvenile mafic melts with the older continental crust at different stages of the Pan-African Orogeny. Slab break-off most likely induced upwelling of the asthenosphere which in turn cause partial melting of the sub-continental lithospheric mantle (SCLM) and the lower crust at the early stage of Late-orogenic to generate 627 ± 4 Ma granites. The magmatism at ca. 580 Ma may have resulted from vertical planar lithosphere delamination as a consequence of transpressive movement along lithospheric scale shear zones which triggered asthenosphere upwelling that facilitated significant crustal melting at the waning stage of the Pan-African orogeny. The presence of post-collisional granite at 627 Ma and distinct isotopic signatures of the E-ENT granitoids compared to those from the NW-Cameroon and Mayo Kebbi domain suggest that E-ENT may have undergone different Pan-African evolution. Graphical abstract: